2016
DOI: 10.3892/br.2016.746
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA methyltransferase polymorphisms with susceptibility to primary gouty arthritis

Abstract: and DNMT3B polymorphisms contribute to gout susceptibility. These polymorphisms were screened for in 336 gout patients and 306 healthy control subjects (from a South China population) for association with gout. The distribution frequencies of DNMT1 rs2228611 AA genotype (P=0.007) and A allele (P=0.002; odds ratio=1.508, 95% confidence �����v�l=1.158�1.964) w��� ����d �� b� ��g��fi����l� ��������d in the gout patients when compared with those in the healthy control subjects. The rs1550117 in DNMT3A and rs242491… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…While the identification of the genes that are targeted by non-coding RNAs remains challenging in vivo, the stability of these molecules and the possibility to easily quantify them in body fluids makes non-coding RNAs attractive circulating biomarkers (54). Additionally, the role of DNA methylation in gout was demonstrated through the discovery of a variant (rs2228611) in the DNA MethylTransferase 1 (DNMT1) gene whose presence is statistically increased in gout patients compared to controls (9). In line with this information, an innovative multi-OMICs study, in which the cell-specific methylome was compared between gout patients and controls, revealed that many differentially methylated gene regulatory genomic sites were associated with IL-1b expression in monocytes (55).…”
Section: Genetics and Epigenetics Of Goutmentioning
confidence: 99%
See 1 more Smart Citation
“…While the identification of the genes that are targeted by non-coding RNAs remains challenging in vivo, the stability of these molecules and the possibility to easily quantify them in body fluids makes non-coding RNAs attractive circulating biomarkers (54). Additionally, the role of DNA methylation in gout was demonstrated through the discovery of a variant (rs2228611) in the DNA MethylTransferase 1 (DNMT1) gene whose presence is statistically increased in gout patients compared to controls (9). In line with this information, an innovative multi-OMICs study, in which the cell-specific methylome was compared between gout patients and controls, revealed that many differentially methylated gene regulatory genomic sites were associated with IL-1b expression in monocytes (55).…”
Section: Genetics and Epigenetics Of Goutmentioning
confidence: 99%
“…Because epigenetics has now been identified as an important player in gouty arthritis, we thought to re-evaluate the impact of diet in light of nutrient-derived epigenetic modifiers. As described in the previous section, a significant number of epigenetic factors potentially affect gout onset and can contribute to further inflammation events worsening the symptoms (9,55). Among such factors influencing epigenetic changes are multiple compounds (listed in Table 1) that are commonly found in one's diet.…”
Section: Diet-derived Epigenetic Modifiersmentioning
confidence: 99%
“…18 Furthermore, DNMT3B-149C>T polymorphism was associated with AITDs 30 but not with primary gout arthritis in Chinese population. 31 The relationship between DNMT3B and MS was also identified recently. This study suggested that messenger ribonucleic acid (mRNA) levels of DNMTs including DNMT3B were increased and demethylation enzymes were lower in demyelinated MS hippocampus than those in myelinated MS hippocampus.…”
Section: Discussionmentioning
confidence: 87%
“…317 A study reported that the DNMT1 rs2228611 polymorphism may function in the development of gout, which is increased in patients with gout. 318 Besides, Wang et al 319 explored gout-associated enrichment of differential DNA methylation in adaptive immunity, including pathways for B and T cell receptor signalling, IL-17 signalling, and Th17 development. In another study, researchers found seven DNA methylation sites in patients with gout that map to seven genes, namely PGGT1B, UBAP1, RAPTOR, INSIG1, ANGPTL2, CNTN5, and JNK1.…”
Section: The Role Of Epigenetic Regulation In Other Metabolic Diseasesmentioning
confidence: 99%